DRUG ABUSE TREATMENT IN PRISONS: A THERAPEUTIC APPROACH - NEGI, DR.VIRENDER; NEGI, MONIKA (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
It’s an acknowledged fact that the prison population in any country comprises that part of thesociety which needs more reformation and correction. And this process of reformation becomesmore complicated and cumbersome if the prisoners or the offenders are addicted to some drugs.These offenders are suffering from Drug dependence and abuse and very much resistant torehabilitation. Therefore the major challenge before the criminal justice system is to deal withthese drug abusers in prisons itself. The incarceration of persons who are found guilty of variouscrimes and who are also chronic substance abusers presents an important opportunity fortreatment. It is a challenging task for the prison authorities and criminal administration becausedrug abuse is that kind of addiction which cannot be treated by the offenders on their own. Andif they are not being treated while custody (both during incarceration and aftercare) there arehundred percent chances of being continued with their drug use even after their release. This isworse situation then. Considering all these threats and issues in light the present criminaladministration system have come up with cost effective drug abuse treatment methods andcorrectional authorities. Now there are techniques and methods to treat these offenders while incustody (both during incarceration and aftercare) and significantly alter their lifestyles.The article is an attempt to study the overall scope of the problem and explores possible methodsand techniques for the drug abuse treatment in prisons and jails. The status of drug abusetreatment is analyzed, and selected treatment approaches are highlighted. Recommendations are also suggested for treatment, research, evaluation, demonstrations, management information,community linkage, training, and technical assistance.